Handbook of physical and mechanical testing of paper and paperboard - Mark, Richard E. (Marcel Dekker, 1983)
This incomparable work-the first part of a two volume set-offers the first cohesive, single source of information on paper testing, examining standard and nonstandard tests as well as scientific principles. It assembles the expertise of twenty international, active researchers working in industry, universities and laboratories.